SISTEM ABSENSI BERBASIS FINGERPRINT DAN PELAPORAN REALTIME MELALUI SMS GATEWAY - Tholib Hariono; Mucharommah Sartika Ami (KH. A. Wahab Hasbullah University, 2018)
In an effort to improve student discipline of school rules, the prevailing student attendance becomes important in order to become a realiable student discipline student's benchmark. But in every school there is often a lot of fraud committed by students such as not going to school without explanation, home school is not appropriate, create a fake license. According to the attendance data that has been in MABU Tambakberas Jombang in the last 5 years has increased the number of student negligence every year. Lack of supervision of parents to students who are mostly students are student at traditional Muslim school Bahrul Ulum Tambakberas Jombang who are parents can not supervise students as much as possible to trigger acts of fraud committed by students. The purpose of making this system is to reduce the level of student neglect and improve student discipline. Supported by fingerprint technology and sms gateway as daily report in andout of student, expected to reduce fraud done by student to control of parent will be discipline through attendance will remain assured and reduce the number of false permit. Keywords: Attendance, SMS Gateway, Fingerprint, Realtime